Project-based learning as a curriculum enhancement of bioinstrumentation in biomedical engineering (LACCEI, 2024)
Bioinstrumentation is an area of interest in biomedical engineering. Currently a great variety of medical devices include instrumentation systems to monitor patients and control body functions with therapeutic purposes. Due to its importance, it has become a topic in the undergraduate degree programs at Latin America. This document analyzed the development and teaching of the courses around this topic in the biomedical engineering program at UNITEC, Honduras. Teachers have detected a difficulty of understanding topics by students, making them to limit the learning scope in the courses. The general objective of this investigation is to propose improvements to these courses, including its contents and methodologies applied in class, as well as the courses in the current curriculum. An analysis was carried out on the current curriculum at UNITEC to identify points of improvement. Also, an international benchmarking was developed to compare the requisites for coursing bioinstrumentation at universities in Central America and Mexico. The improvements proposal was developed with this data and the construction of a state of the art. The two identified areas that need improvement are the learning methodologies applied and the approach of activities in laboratories. Project-based learning has been identified as the best option to boost research and development of medical devices in the country, leading to improve the curriculum of biomedical engineers.